2020
DOI: 10.1111/joss.12606
|View full text |Cite
|
Sign up to set email alerts
|

Using projective techniques and Food Neophobia Scale to explore the perception of traditional ethnic foods in Central Mexico: A preliminary study on the beverage Sende

Abstract: Foods considered ethnic are produced and consumed in a specific region. As well it has been documented that consumers expresses fear of the intention of eating new foods. Furthermore, the perception of the Mexican consumers toward ethnic foods has been scarcely studied. The aim of this work was to explore the perception toward Sende-a traditional ethnic Mazahua beverage of low alcoholic content, produced from germinated corn, dried, cooked and fermented-using word association (WA) and Food Neophobia Scale (FNS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 42 publications
1
17
1
4
Order By: Relevance
“…We managed to identify four clusters with the factors that emerged in the course of the analysis. Unlike our research, most other surveys-such as Bernal-Gil et al [52] and Paupério et al [28]-identified three clusters, but there were two-cluster solutions as well (e.g., [53]). Given that the different surveys used a different number of items in the FNS to serve as the basis of their analysis, and various numbers of factors with different compositions were created with different factor loadings, the possibilities of international comparisons of cluster analyses carried out with these factors is, therefore, severely limited.…”
Section: Discussioncontrasting
confidence: 96%
“…We managed to identify four clusters with the factors that emerged in the course of the analysis. Unlike our research, most other surveys-such as Bernal-Gil et al [52] and Paupério et al [28]-identified three clusters, but there were two-cluster solutions as well (e.g., [53]). Given that the different surveys used a different number of items in the FNS to serve as the basis of their analysis, and various numbers of factors with different compositions were created with different factor loadings, the possibilities of international comparisons of cluster analyses carried out with these factors is, therefore, severely limited.…”
Section: Discussioncontrasting
confidence: 96%
“…While the FNS has been proven successful in measuring consumer receptivity to novel foods [24,25], it is not clear if it can be used to measure different dimensions of food neophobia related to biofortified foods. Biofortified foods, particularly those involving visible nutrition traits, have two significant attributes that may affect the food decision process, i.e., modified nutrition and color change.…”
Section: Literature Background and Hypothesis Development Food Neophobia And Consumer Acceptance Of Novel Foodsmentioning
confidence: 99%
“…Posteriormente, se calcularon los puntajes de la sumatoria de los 10 ítems de la escala por cada sujeto o participante, esto se realizó con la finalidad de obtener el valor de neofobia alimentaria por cada participante, el cual podía oscilar entre 10 y 50 (Pliner y Hobden, 1992;Soucier, Doma, Farrel, Leith-Bailey y Duncan, 2019). Además, se calcularon las medidas de tendencia central y dispersión (media y desviación estándar) por cada una de las variables de la ENA La estructura de la ENAfue evaluada a partir del método de Análisis de Componentes Principales (Fernández-Ruíz et al, 2013;Bernal-Gil et al, 2020). El Análisis de Componentes Principales es una herramienta de la estadística multivariada que transforma un conjunto de variables que pueden estar relacionadas, en una serie de variables que están linealmente correlacionados o también conocidos como componentes principales (Zakaira, 2014).…”
Section: Análisis De Informaciónunclassified
“…Es de destacar que el valor de la ENA fue de 26.00±6.49, lo que sugiere que los niveles de neofobia alimentaria, entre la población de estudio, es baja. Los resultados guardan consistencia con otras investigaciones que han empleado la ENA en diferentes contextos en México (Salgado et al, 2016;Bernal-Gil et al, 2020) Otro aspecto a destacar es que el estudio fue llevado a cabo en tiempos de la pandemia de COVID-19, lo que sugeriría que al menos en este sector de la población, la epidemia causada por el virus SARS-CoV-2 no ha afectado significativamente en los niveles de miedo o rechazo de alimentos nuevos extraños entre algunos sectores de la población joven del país. Guzek et al (2021) reportaron también que algunos consumidores jóvenes presentaron bajos niveles de neofobia alimentaria en tiempos de COVID-19.…”
Section: Neofobia Alimentaria Estudiantes Universitariosunclassified
See 1 more Smart Citation